2019
DOI: 10.1590/1678-5150-pvb-6328
|View full text |Cite
|
Sign up to set email alerts
|

Salmonellosis in calves without intestinal lesions

Abstract: Salmonellosis is a known cause of enteric disorders in calves. However, cases in the septicemic form may not present enteric lesions, which may lead the veterinary practitioner to not suspect salmonellosis, compromising the diagnosis. The current study describes the epidemiological, clinical, pathological and immunohistochemical aspects of septicemic salmonellosis in calves without enteric lesions. The protocols involving bovine material submitted to the Pathology Laboratory (LAP) of the “Faculdade de Medicina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…Similar samples were proposed by Holschbach and Peek [31]. In accordance with Guizelini et al [32] and Ramos et al [35], the main macroscopic lesions observed in our work were enteritis with or without fibrin, mesenteric lymphadenomegaly, and hepatomegaly. In contrast to what was reported by Pecoraro et al [17], in our work, macroscopic lesions in the lungs and spleen were less frequent.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar samples were proposed by Holschbach and Peek [31]. In accordance with Guizelini et al [32] and Ramos et al [35], the main macroscopic lesions observed in our work were enteritis with or without fibrin, mesenteric lymphadenomegaly, and hepatomegaly. In contrast to what was reported by Pecoraro et al [17], in our work, macroscopic lesions in the lungs and spleen were less frequent.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, in all S. Dublin cases, macroscopic intestinal lesions were absent, and calves did not show diarrhea except for one case. Similar results were observed by Guizelini et al [32] in Brazil. Assays performed with this serotype have shown that the aflagellated types isolated from the bloodstream can generate a lower intestinal inflammatory response and increased invasiveness [9].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study and previously cases [1,19] show that septicemic salmonellosis is endemic in Brazil and may cause high losses to the livestock. Due to its zoonotic character, in our country, salmonellosis is a disease that has official surveillance guidelines only in aviculture [20], despite its also being a potential cause of economic losses in beef cattle.…”
Section: Discussionsupporting
confidence: 73%
“…According to the WHO, since 1990, Salmonella Enteritidis has been considered the most common cause of gastroenteritis worldwide (Chaitram et al 2003 ) and salmonellosis in bovine, ovine, and poultry (Suh and Song 2006 ; Firoozeh et al 2012 ; Dutta et al 2012 ; Guizelini et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%